A Physic Nut Stress-Responsive HD-Zip Transcription Factor, JcHDZ07, Confers Enhanced Sensitivity to Salinity Stress in Transgenic Arabidopsis - Tang, Yuehui; Bao, Xinxin; Wang, Shuang; Liu, Yan; Tan, Jie; Yang, Mengxia; Zhang, Mengyuan; Dai, Rongrong; Yu, Xinrong (Frontiers in Plant Science, 2019)
HD-Zip (Homeodomain-leucine zipper) transcription factors are reported to play crucial roles in the growth, development and stress responses of plants. However, there is little knowledge of the molecular mechanisms involved in physic nut’s stress tolerance generally, or the functions of its HD-Zip genes. In the present study, a HD-Zip family transcription factor, designated JcHDZ07, was isolated from physic nut. Expression profile analysis showed that salinity stress inhibited the expression of JcHDZ07. Transient expression of JcHDZ07-YFP in Arabidopsis protoplast cells revealed that JcHDZ07 was a nuclear-localized protein. Additionally, no obvious difference in growth and development between wild-type and JcHDZ07-overexpressing plants was observed in the absence of stress. Our results further indicated that JcHDZ07 overexpressing transgenic plants had lower proline contents, lower survival rates and activities of catalase and superoxide dismutase, but higher relative electrical leakage and malonaldehyde contents compared with wild-type plants under salinity stress conditions, suggesting that overexpression of JcHDZ07 confers enhanced sensitivity to salinity stress in transgenic Arabidopsis. Expression of salt stress-responsive genes were upregulated in leaves of transgenic plants under salinity stress, but less strongly than in wild-type plants. Collectively, our results suggest that JcHDZ07 functions as an important regulator during the process of plant responses to salinity stress.